SOME SAMPLE TEST RESULTS FOR ABRASIVE WEAR - Valeri A. Petrovsky; Anatoliy R. Ruban; Ali Salamekh (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Abstract. Objectives In general, the reliability of dredgers is highly dependent on the performance of the scoop chain, a working body that is subject to high dynamic loads, a significant part of which falls on the swivel. The wear of the scoop chain swivel is complicated by the ingress of abrasive particles into the gap. Aims and tasks: increasing the wear resistance of the scoop chain swivel having an abrasive component of the general destruction process; determination of the abrasive wear durability of test materials; analysis of test results and recommendations for improving the reliability and efficiency of the swivel. Methods Comparative tests for the abrasive wear of samples manufactured according to proprietary technologies for the assembly of parts from 38HN3MA and 110G13L steels; samples manufactured from 38HN3MA and 110G13L steels using a modified manufacturing technology; surfacing using E-50-UONI 13/55 electrodes followed by subsequent hardening and without it; surfacing using E-190H5S7-LEZ-Т-590-NG electrodes without hardening and with surface-plastic deformation. The samples were tested for abrasion against fixed abrasive particles at pressures of 27.3 kPa and 47.4 kPa. Results The abrasion resistance characteristics are obtained for samples: (1) made of 38HN3MA, 110Г13Л steels, manufactured by the factory technology and adopted as the standard; (2) made of 38HN3МА steel after quenching and low tempering; (3) made of 110G13L steel after quenching and surface-plastic deformation; (4) after surfacing using E-50-UONI 13/55 electrodes without hardening, hardened by surface-plastic deformation and hardened by carburising, quenching and low tempering; (5) after surfacing using E-190H5S7-LEZ-Т-590-NG electrodes without hardening and with hardening by surface-plastic deformation. The dependences of the mass Δm and the linear Δl abrasions, as well as the relative wear resistance Im, Il on the hardness, are plotted. Conclusions Changing and supplementing the factory technologies of the swivel details manufactured from 38HN3MA and 110G13L steels will increase the wear resistance of the friction pair. Restoration of worn fingers by surfacing using E-50-UONI 13/55 electrodes with subsequent carburising, quenching and low tempering can be recommended for use in operation. Surfacing using E-190H5S7-LEZ-Т-590NG electrodes with subsequent surface-plastic deformation will significantly increase the wear resistance of the restored fingers.